2016
DOI: 10.1007/s00467-016-3372-y
|View full text |Cite
|
Sign up to set email alerts
|

Xenopus: leaping forward in kidney organogenesis

Abstract: While kidney donations stagnate, the number of people in need of kidney transplants continues to grow. Although transplanting culture-grown organs is years away, pursuing the engineering of the kidney de novo is a valid means of closing the gap between the supply and demand of kidneys for transplantation. The structural organization of a mouse kidney is similar to that of humans. Therefore, mice have traditionally served as the primary model system for the study of kidney development. The mouse is an ideal mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 69 publications
0
12
0
Order By: Relevance
“…Thus, a Gda effect on kidney functioning or maturation to mesonephroi might be expected. Moreover, knockdown of Xenopus GDAs resulted in edema formation, which has been shown to be indicative of kidney malfunction (Wessely and Tran, 2011; Krneta-Stankic et al, 2017). Nevertheless, at the Xenopus developmental time point that we performed our studies, the pronephroi has still not matured to mesonephroi, thus, it remains to be determined if Gda has an effect on kidney maturation to mesonephroi, or if the effect is restricted to kidney function.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, a Gda effect on kidney functioning or maturation to mesonephroi might be expected. Moreover, knockdown of Xenopus GDAs resulted in edema formation, which has been shown to be indicative of kidney malfunction (Wessely and Tran, 2011; Krneta-Stankic et al, 2017). Nevertheless, at the Xenopus developmental time point that we performed our studies, the pronephroi has still not matured to mesonephroi, thus, it remains to be determined if Gda has an effect on kidney maturation to mesonephroi, or if the effect is restricted to kidney function.…”
Section: Discussionmentioning
confidence: 99%
“…Still, we wondered whether Gda might be important for kidney function. It has been demonstrated that an altered osmoregulatory function of the kidney leads to edema formation due to water retention (Wessely and Tran, 2011;Krneta-Stankic et al, 2017) and evaluation of edema has been widely used to assess kidney function (Getwan and Lienkamp, 2017;Krneta-Stankic et al, 2017). Thus, we used an antisense oligonucleotide to knock down (KD) gda by 50% (Fig.…”
Section: Xenopus Gda Is Strongly Expressed In the Embryonic Kidney Anmentioning
confidence: 99%
“…In human and murine organisms, the pronephros and mesonephros are transient organs and degenerate at the embryonic stage [ 2 ]. Unlike in lower vertebrates, such as zebrafish and Xenopus, where the pronephros is functional at the embryonic and larval stages [ 24 , 25 ], the metanephros begins at E 32 in human and E 10.5 in mice [ 26 ]. Notably, the metanephros is permanent and will develop into a functional adult kidney in mammals.…”
Section: Wnt Signaling In Kidney Developmentmentioning
confidence: 99%
“…Although the external development of X. laevis embryos allows for live imaging of many tissues, [ 24 ] live imaging of the kidney is difficult because there are currently no live markers. To facilitate the study of the dynamic cellular movements that occur during nephrogenesis, we generated a X. laevis transgenic line that labels the kidney cells.…”
Section: Introductionmentioning
confidence: 99%